Artificial Intelligence Research in Africa and the Importance of Recall Concept - Pouris, Anastassios; Thirion, Androniki (Information Research Communications, 2025)
Introduction This article investigates the publication performance of African countries in the field of Artificial Intelligence (AI), with a particular emphasis on the methodological importance of recall in scientometric analyses. Recall rate plays a pivotal role in shaping research funding decisions, influencing resource allocation and determining the effectiveness of funded projects. Our investigation reveals that several stakeholders publish research with limited emphasis on the shortcomings of recall. This potentially undermines the robustness of policy recommendations and validity of findings. This article aims to rectify the findings of deficient investigations related to AI research in Africa and provide findings closer to reality. Methodology In this article using an extensive search strategy comprising over 387 search terms, 19 AI-focused journals, and the Web of Science category “Computer Science: Artificial Intelligence,”. Results we identify a significant growth in AI publications across Africa-from 1,659 in 2014 to 6,756 in 2023. Egypt leads with 11,920 publications and it is followed by South Africa (7,221), Tunisia (6,987), and Morocco (6,013). China is identified as a key funder of AI research in Africa. Collaboration patterns show a preference for international partnerships over intra-African collaboration. Conclusion The article concludes with policy recommendations and a critique of methodological practices in AI-related scientometric studies.
Keywords: Africa; Artificial Intelligence; Methodologies; Recall concept; Scientometrics.